Analisa Data Rekam Medis Menggunakan Teknik Data Mining Association Rules Dengan Algoritma Clustering - Edy Kurniawan (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Patient information data located in medical centers and hospitals are in theform of ICD codes. Medical Record data is not just a pile of files, but can beused to extract the information contained therein. Some information thatcan be utilized is the information group of diseases that often suffered bypatients in the hospital. Information group of this disease can be utilized bythe manager in developing services to patients. From the side of the patientcan take advantage of treatment goals are more appropriate target inaccordance with the disease he suffered. To determine the analysis of thisstack of medical records using groupings, including grouping of regions,gender groupings, age groupings, and ICD code groupings. In this studyICD code used is ICD 10. Preposecing medical record data is divided intotwo, first data training and second is test data. From the results of dataprocessing using cross validation 10 fold obtained the most optimal resultswith an accuracy of 53.8% Keywords: Clustering Algorithm, Data Mining, Medical Record